1998
DOI: 10.1128/aem.64.1.7-13.1998
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Vibrio vulnificus Biotypes in Danish Marine Environments

Abstract: During the unusually warm summer in Denmark in 1994, 11 clinical cases of Vibrio vulnificus infection were reported. These reports initiated an investigation of the occurrence of V. vulnificus biotypes in Danish marine environments. Samples of coastal water, sediment, shellfish, and wild fish were analyzed by preenrichment in alkaline peptone water amended with polymyxin B (2.0 × 104 U/liter) followed by streaking onto modified cellobiose-polymyxin B-colistin agar. V. vulnificus-like colonies were tested with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(42 citation statements)
references
References 46 publications
4
38
0
Order By: Relevance
“…Immediate chilling after the harvest and storage at a low temperature (0-4 1C) can lower its cultivable population to reduce its threat (Cook & Ruple, 1992). According to previous findings, the V. vulnificus biotype 1 strains, capable of infecting humans, is overwhelmingly dominant (c. 99%) among the total V. vulnificus population in coastal and marine environments (Hor et al, 1995;Høi et al, 1998). However, a latest study has revealed that among coastal biotype 1 strains the virulence-correlated gene responsible for human infection (vcgC) comprises a minor fraction of the total population (c. 15%) but increases its percentage as the water temperature increases (Warner & Oliver, 2008).…”
Section: Vibrio Vulnificus In Coastal Seaweed and Public Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Immediate chilling after the harvest and storage at a low temperature (0-4 1C) can lower its cultivable population to reduce its threat (Cook & Ruple, 1992). According to previous findings, the V. vulnificus biotype 1 strains, capable of infecting humans, is overwhelmingly dominant (c. 99%) among the total V. vulnificus population in coastal and marine environments (Hor et al, 1995;Høi et al, 1998). However, a latest study has revealed that among coastal biotype 1 strains the virulence-correlated gene responsible for human infection (vcgC) comprises a minor fraction of the total population (c. 15%) but increases its percentage as the water temperature increases (Warner & Oliver, 2008).…”
Section: Vibrio Vulnificus In Coastal Seaweed and Public Healthmentioning
confidence: 99%
“…(DePaola et al, 1994Wright et al, 1996;Høi et al, 1998). Two major biotypes of V. vulnificus are known: biotype 1 is related to human infection while biotype 2 is exclusively found among diseased fish, particularly eel (Høi et al, 1998). Recent findings indicate the spread of pathogenic V. vulnificus strains into new regions of the earth, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Vibrio vulnificus is part of the normal microbiota of estuarine waters and occurs in high numbers in molluscan shellfish around the world, particularly in warmer months. This opportunistic pathogen is common in estuarine waters and has been isolated from a range of different environmental sources, including water, sediment and seafood produce (O'Neill et al, 1992;DePaola et al, 1994;Høi et al, 1998;Bisharat et al, 1999;do Nascimento et al, 2001;Baffone et al, 2006;Baker-Austin et al, 2010). Human infections associated with this bacterium originate from two distinct sources: consumption of seafood (primary septicemias) or exposure to seawater or seafood products (wound infections).…”
Section: Introductionmentioning
confidence: 99%
“…A component of the heterotophic bacteria is the genus Vibrio spp., one of the most common bacterial genera in marine environments. Some species may cause infections in humans and aquaculture resources (Baross & Liston, 1970;Kaneko & Colwell, 1973;Hi et al, 1998). Physicochemical factors determine to a great extent the growth rate and biomass production of heterotrophic bacteria and Vibrio spp.…”
Section: Introductionmentioning
confidence: 99%